Deification and sanctification in the dialogue between the Finnish Lutheran School and the Chinese Neo‐Confucian School. Issue 1 (27th December 2021) - GAO, Yuan
Abstract: The ideal of becoming divine occupies a central position not only in Lutheran theology but also in Confucian traditional teachings. While expectations of these two traditions on the ideal of human life look different, it does not mean that they do not share any theoretical convergence. The present article explores an in‐depth look into the doctrine of deification (θεοποιεiν; theōsis) in the Finnish interpretation of Luther, where Tuomo Mannermaa (1937–2015) developed originally his theory in the Lutheran‐Orthodox dialogue, and forms a new landscape for building up a connection between the Finnish Lutheran School and Chinese Neo‐Confucianism in their accounts of deification (成神) and sanctification (成聖). The main objective of this study is to clarify the historical doctrine of theōsis in Luther's theology by analyzing the hermeneutic approach of divinization in the Finnish School and its contributions; and furthermore, to discover possibilities of dialogue between deification and sanctification and new approaches to them. Attending to distinctive features of the theology of hope in these two intellectual circles, this study untilizes the perspective of the deification of emotions, which would become a new approach in deepening the theory of deification in the Lutheran‐Confucian dialogue.